The Hallmarks of Cancer as Ecologically Driven Phenotypes - Somarelli, Jason A. (Frontiers in Ecology and Evolution, 2021)
Ecological fitness is the ability of individuals in a population to survive and reproduce. Individuals with increased fitness are better equipped to withstand the selective pressures of their environments. This paradigm pertains to all organismal life as we know it; however, it is also becoming increasingly clear that within multicellular organisms exist highly-complex, competitive, and cooperative populations of cells under many of the same ecological and evolutionary constraints as populations of individuals in nature. In this review I discuss the parallels between populations of cancer cells and populations of individuals in the wild, highlighting how individuals in either context are constrained by their environments to converge on a small number of critical phenotypes to ensure survival and future reproductive success. I argue that the hallmarks of cancer can be distilled into key phenotypes necessary for cancer cell fitness, including i) survival & resource acquisition, ii) predator avoidance, and iii) reproduction. I posit that for therapeutic strategies to be maximally beneficial, they should seek to subvert all of these ecologically-driven phenotypic responses.